Coalition politics and the iraq war : determinants of choice - Baltrusaitis, Daniel F. ([S.l.] : Lynne Rienner Publishers, 2009)
John Cameron draws on power-based approaches to the study of democratization as he thoughtfully explores efforts by indigenous and peasant groups to gain control of local governments and deepen democracy in Bolivia, Ecuador, and Peru. Cameron addresses three fundamental questions: What factors best explain the success or failure of local political movements in the Andes? What forms of democracy are emerging in indigenous- and peasant-controlled municipalities? What are the impacts of municipal democratization on the well-being and political identities of the citizenry? As he elucidates his results, he reminds readers that, in the midst of some of the most exclusionary and elite-dominated systems of local government in Latin America, political struggles for democracy are having a profound impact.
Keywords: Coalitions; Germany; Iraq War (2003-2011); Korea (South); Military participation--Foreign; Political science; Turkey